High-connectivity species drive macroinvertebrate community stability in river ecosystems - Liu, Yang; Zhang, Min; Peng, Wenqi; Qu, Xiaodong (Frontiers in Ecology and Evolution, 2025)
Identifying keystone species and investigating their ecological regulatory role will help to prioritize important species and gain a better understanding of community stability mechanisms. In this study, macroinvertebrates were sampled from Chishui River (CSH, an undammed river) and Heishui River (HSH, a dammed river) in April 2018, 2019, and 2020. Macroinvertebrate networks were constructed to identify keystone species and reveal their ecological regulatory role on community stability. The results showed that the loss of high-connectivity species had a greater impact on macroinvertebrate community stability than the loss of high-biomass and high-density species, which indicated that high-connectivity species with low abundance were keystone species. Moreover, these were primarily composed of less abundant species. The functional feeding traits of keystone species were dominated by predators in the undammed river and prey (i.e., collector-gatherers) in the dammed river, which suggested that the construction of dams transformed the functional feeding groups of keystone species. In addition, after the loss of keystone species, the decline rates of the half of the robustness (R50), survival area (SA), and network connectivity robustness (CR) in the dam-constructed reaches were higher than those in other reaches. This result demonstrated that the construction of dams may reduce the resistance of macroinvertebrate communities to keystone species loss. This study provides an important scientific basis for conserving aquatic life and maintaining the structural and functional stability of river ecosystems.